IMF Staff papers : Volume 12 No. 1. (IMF Staff Papers; IMF Staff Papers, 1965)
This paper focuses on various aspects of the Euro-dollar market. The market in Euro-dollars is a wide and complicated one spread over six continents and bound together by a network of cable, telex, and telephone communication. The paperwork in the market tends to confirm rather than to initiate transactions. The financial standing of the banks in the market is such that transactions are based on names and do not involve collateral and guarantees. Some Euro-dollar funds are used to finance commercial loans and other domestic transactions, either in the form of dollars or in local currency purchased with dollars. There has been a large amount of such transactions in Germany, Italy, and Japan, and smaller amounts in many other countries, including Switzerland. The role of Euro-dollars as a money market instrument has some important implications. A substantial part of the Euro-dollar pool circulates and recirculates endlessly among banks. The rapid development of the Euro-dollar market, the facilities offered by a new money market instrument, and the increased, although gentlemanly, competition among banks on both the domestic and international scene, have been accompanied by a certain amount of exuberance.